2018
DOI: 10.18410/jebmh/2018/405
|View full text |Cite
|
Sign up to set email alerts
|

Review of Sigmoid Volvulus: A 5 Years Experience in Tertiary Care Hospital, Visakhapatnam

Abstract: BACKGROUNDSigmoid volvulus is a common cause of large bowel obstruction in developing countries where it affects relatively young people compared to developed countries and its mortality remains significant in patients with late diagnosis. The aim of this work is to assess the clinical presentation, management and outcome of sigmoid volvulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 17 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…The first description with reference to the volvulus was found in the records of Egypt in the Ebers papyrus and mentioned that the volvulus could resolve spontaneously or present a picture of intestinal necrosis; from 1500 BC, it is recognized that detortion of the intestinal loop is crucial for the definitive resolution of the picture, and there are also records made by Hippocrates where suppositories and insufflation were used by mechanical instruments introduced in the anus in order to generate decompression [6]. However, the first description coined with the term Sigmoid volvulus was made by Von Rokitansky in 1836, demonstrating a condition in which the sigmoid wraps itself and its own mesentery, causing a closed loop intestinal obstruction that, if not treated, presented complications such as intestinal ischemia, gangrene, and perforation [7].…”
Section: Recordmentioning
confidence: 99%
See 4 more Smart Citations
“…The first description with reference to the volvulus was found in the records of Egypt in the Ebers papyrus and mentioned that the volvulus could resolve spontaneously or present a picture of intestinal necrosis; from 1500 BC, it is recognized that detortion of the intestinal loop is crucial for the definitive resolution of the picture, and there are also records made by Hippocrates where suppositories and insufflation were used by mechanical instruments introduced in the anus in order to generate decompression [6]. However, the first description coined with the term Sigmoid volvulus was made by Von Rokitansky in 1836, demonstrating a condition in which the sigmoid wraps itself and its own mesentery, causing a closed loop intestinal obstruction that, if not treated, presented complications such as intestinal ischemia, gangrene, and perforation [7].…”
Section: Recordmentioning
confidence: 99%
“…On the other hand, the incidence of intestinal volvulus, regardless of the cause and origin, represents variable ranges according to the statistics available; it is reported as 4% of all cases of intestinal obstruction in developed countries and up to 50% of developing countries. Regarding gender distribution, it has been proposed that the predisposition of men to sigmoid colon volvulations is secondary to the fact that the female pelvis has more space for spontaneous reduction of volvulations [7]. A study conducted in the endemic population of Peru showed that fluctuations in temporary rains condition variations in the chances of infection in domestic and human animals [10].…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
See 3 more Smart Citations